Molecular characterization of antibiotic resistant bacteria and antimicrobial residues in the dairy milk in India - Dey, Tushar K.; Shome, B.; Deka, Ram Pratim; Shome, R.; Lindahl, Johanna F. (International Livestock Research Institute, 2022)
Introduction: Food safety is a great concern in low- and middle-income countries. Milk and milk products are staple foods that are consumed regularly by infants to adults in India and worldwide. However, exposure to antibiotic-resistant bacteria in milk could pose a risk to public health. This project was conducted to understand milk safety, by assessing antibiotic residues and resistant bacteria in the milk from dairy farmers and vendors. Methods: The 729 milk samples were collected from two Indian states, and analyzed for the presence of food pathogens following standard laboratory procedure. The disc diffusion antibiotic susceptibility testing (ABST) was done to screen resistant bacteria. The resistant isolates by ABST were then studied by Polymerase chain reaction (PCR) genotyping to detect methicillin resistance, extended-spectrum beta-lactamases (ESBL), Metallo-beta-lactamases (MBL), and AmpC beta-lactamase’s (AmpC). Antibiotic residues were assessed using rapid tests, and lateral flow tests. Results: The isolated gram-positive bacteria were found to be 74% (n=243) Staphylococcus spp. of which only 6% (n=14) harbored methicillin resistance (14 mecA and 2 mecC genes). Among the isolated gram-negative bacteria, 13% (n=43) of the isolates were resistant consisting of E. coli, Klebsiella spp., and Shigella spp. 59 % (n=7) of them were carrying ESBL genes, 60% AmpC (n=26), 14% MBL (n=6), 7% MBL+AmpC (n=3) and 2% ESBL+ AmpC (n=1). Antibiotic residues detected included beta-lactam, chloramphenicol, quinolone, tetracycline, oxytetracycline, sulfa drugs, streptomycin, and macrolides. Conclusion: The collected milk sample was found to be contaminated with 6% methicillin-resistant Staphylococcus spp. and 13% with E. coli, Klebsiella spp., and Shigella spp with ESBL, MBL, and AmpC resistance. On the other hand, the existence of antibiotic residues beyond MRL along with pathogenic bacteria with a signature of resistance genes in farm animals as reservoirs and their dissemination through the food chain poses a public health threat.